Nano-mechanisms of connection in the solid phase of tungsten and tantalum in the manufacture of a neutron source target - Borts, B.V.; Vorobyov, I.A.; Zelinsky, A.Yu.; Karnaukhov, I.M.; Lopata, A.A.; Parkhomenko, A.A.; Patochkin, I.V.; Tkachenko, V.I. (Problems of Atomic Science and Technology, 2023)
Nano-mechanisms of solid-phase bonding of tungsten and tantalum, which are implemented in the manufacture of a neutron source target for the research nuclear facility (RNF) of NSC KIPT, are considered. This facility is a new type of nuclear reactor, in the core of which the intensity of the nuclear fission reaction of the uranium isotope ²³⁵U is controlled by an electron accelerator. An installation for joining metals in the solid phase is described, its parameters are given, as well as the parameters of the joined metals. An electron-probe X-ray spectral analysis of the interface between the samples was carried out. The physical foundations of the nano-mechanism of bonding in the solid phase of tungsten and tantalum at the dynamic and isostatic stages at hot vacuum pressing are formulated. Experimental data on the relative temperature convergence of rolls at the dynamic and isostatic stages of hot vacuum pressing have been obtained. Розглянуто наномеханізми з’єднання у твердій фазі вольфраму та танталу, що реалізуються під час виготовлення мішені нейтронного джерела для дослідницької ядерної установки НДК ПЯС ННЦ ХФТІ. Ця установка є новим типом ядерного реактора, в активній зоні якого інтенсивність протікання ядерної реакції поділу ізотопу урану ²³⁵U керується прискорювачем електронів. Описано установку для з’єднання металів у твердій фазі, наведено її параметри, так само як і параметри металів, що з’єднуються. Проведено електронно-зондовий рентгеноспектральний аналіз межі з’єднання зразків. Отримано експериментальні дані щодо температурного сходження валків на стадіях: динамічній і ізостатичного гарячого вакуумного пресування.